PENANGANAN NON BEDAH PADA TRAUMA KAPITIS - Tri Makmur; Fazidah Aguslina Siregar (Jurnal Penelitian Keperawatan Medik, 2020)
Capitis trauma is a problem in the field of neurology, as the most common cause of death in young adults (<45 years) and a major cause of disability. Of the 2 million emergency patients, 25% are caused by capitis trauma, which can cause neurological disorders and structural damage to the brain resulting in decreased consciousness. In developing countries, including Indonesia, the frequency of capitis trauma tends to increase. Capitis trauma can occur at any age, most often regarding the productive age group (15-44 years). The frequency of capitis trauma is higher in males than females with a ratio of 4: 1. The most common cause is due to accidents by 60%. Capitis trauma in terms of neurological aspects requires operative therapy and non-operative therapy. Non-operative treatment can be done by maintaining the airway / ventilation, maintaining fluid balance, maintaining temperature, neurological examination and administration of drugs such as dexamethasone, anti-seizure administration, administration of hypertonic fluids such as manithol and administration of stress ulcer drugs.